Spectral-domain optical coherence tomography findings in polypoidal choroidal vasculopathy suggest a type 1 neovascular growth pattern - Alshahrani ST (Dove Medical Press, 2014)
Saeed T Alshahrani,1,2 Hanan N Al Shamsi,2 Eman S Kahtani,2 Nicola G Ghazi2,3 1King Fahad Specialist Hospital, Dammam, Saudi Arabia; 2King Khaled Eye Specialist Hospital, Riyadh, Saudi Arabia; 3University of Virginia, Department of Ophthalmology, Charlottesville, VA, USA Purpose: To report spectral-domain optical coherence tomography (SD-OCT) findings in polypoidal choroidal vasculopathy (PCV).Patients and methods: Seventeen eyes of 15 consecutive patients diagnosed with PCV based on typical clinical and angiographic findings were imaged with macular SD-OCT including line scans passing through the polyps.Results: SD-OCT findings included typical and atypical retinal pigment epithelial (RPE) detachments and subretinal and intraretinal fluid in all eyes. In the areas corresponding to the polypoidal lesions, well-delineated round-oval, sub-RPE cavities were present and were adherent to the posterior surface of the detached RPE above Bruch membrane. No retinal or choroidal connections to the cavities were noted.Conclusion: These SD-OCT findings document that the vascular lesions in PCV are not located in the inner choroid, but in the sub-RPE space, suggesting that PCV is a variant of type 1 choroidal neovascularization rather than a distinct clinical entity as initially thought. Keywords: choroidal neovascularization, retinal pigment epithelial detachments, vascular lesion, SD-OCT, type 1 choroidal neovascularization